Size Selectivity of 40 mm Square Mesh Codend with respect to Yellowstriped Goatfish, Upeneus vittatus (Forsskal, 1775) and Orangefin Ponyfish, Leiognathus bindus (Valenciennes, 1835) - R., Raghu Prakash; G., Rajeswari; U., Sreedhar (Fishery Technology, 2025)
Yellowstriped goatfish, Upeneus vittatus (Forsskal, 1775) and Orangefin Ponyfish, Leiognathus bindus (Valenciennes, 1835) are widely exploited by the trawl fishery. Due to the use of codends with conventional small diamond mesh in the trawl nets, large quantities of juveniles of these species are landed along the east coast of India. The size selectivity of 40 mm square mesh codend for Upeneus vittatus and Leiognathus bindus was studied with a 30 m demersal trawl, following covered codend method. The L25, L50 and L75 values for Upeunus vittatus were 10.0, 11.22 and 12.4 cm respectively. Selection factor, selection range and selection ratio for Upeneus vittatus were 2.8 and 2.43 and 0.6 respectively. The L25, L50 ,L75 values for Leiognathus bindus were 5.52, 7.7 and 9.88 cm respectively. Selection factor, selection range and selection ratio for Leiognathus bindus were 1.92, 4.36 and 1.09 respectively.